At-Tasawwuf and Neoplatonic Philosophy - Uždavinys, Algis (Acta Orientalia Vilnensia, 2001)
Despite the clear evidence that Sufism derived from the Qur’an, or rather interpretations of the selected Qur’anic verses and sayings of the Prophet, its metaphysical and spiritual dimensions are closely tied with the late Hellenic philosophy and especially Neoplatonism. The Sufi sages, such as Dhu’l-Nun al-Misri, Ibn ’Arabi, Shabistari, Suhrawardi and others, accepted, transformed and adapted to the Islamic context many ideas of metaphysics and spiritual psychology which originated in the Middle Platonic and Neoplatonic milieu. Alexander of Aphrodisias, Numenius, Plotinus, Jamblichus, Syrianus, Proclus or Damascius as philosophers under their own proper names are almost unknown to the Muslims and the Middle Platonic and Neoplatonic doctrines are often presented under the name of Aristotle. However, the anonymous Neoplatonic ideas are widely used, though sometimes they may be understood just as the manifestations of the same transcendental archetypes.